Physicochemical Properties of analogs α-Aminophosphonates Drugs Determined via Molecular Dynamics Simulation - Sabbaghzadeh, Reihaneh (Asian Pacific Journal of Cancer Biology, 2019)
Objective: Cyclin-dependent kinases (CDKs, play important roles in cell cycle regulation. Since deregulation of cyclins and/or alteration or absence of inhibitors has been associated with many cancers, there is strong interest in CDKs inhibitors that could play an necessary role in the discovery of a new family of antitumor agents. Material and Methods: Molecular modeling is used to design new materials, which the correct prediction of physical properties of realistic systems is required. Gromacs is an tool to perform molecular dynamics simulations and energy minimization of bimolecular systems which commonly consists of several tens to thousands of amino acid residues. From the simulations the first 100 ps were regarded as equilibration, leaving 900 ps for analysis purposes. Results: Thermodynamic properties density, potential energy, temperature, and pressure are given. In this results tetramethyl ((1,4-phenylenebis (azanediyl)) bis ((4-chlorophenyl) methylene)) bis (phosphonate) was found to be the better selective known inhibitor for cyclin-dependent kinase2 because it shown lowest energy. Conclusion: The phosphoric acid moiety is considered to bind to the affected protein more actively than the corresponding carboxylic acid because of its di anionic character.